2009
DOI: 10.1007/978-3-642-02583-9_49
|View full text |Cite
|
Sign up to set email alerts
|

Designed to Fit: Challenges of Interaction Design for Clothes Fitting Room Technologies

Abstract: This paper uncovers issues in the design of camera-based technologies to support retail shopping in a physical store, specifically clothes shopping. An emerging class of technology is targeting the enhancement of retail shopping, including the trying on of clothing. Designing such systems requires careful considerations of physical and electronic design, as well as concerns about user privacy. We explore the entire design cycle using a technology concept called the Responsive Mirror through its conception, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A key question to explore was whether and in what ways do such systems provide benefit to users: shoppers, sellers and companions. In one study [4], users ranked both of the digital media reflection types offered by the Responsive Mirror (previous fitting reflection and similar/dissimilar shirt reflection) higher than a plain mirror. On the other hand, neither type of digital reflection changed the appeal of the shirts nor ultimately their decision to buy a shirt.…”
Section: Summary Of User Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…A key question to explore was whether and in what ways do such systems provide benefit to users: shoppers, sellers and companions. In one study [4], users ranked both of the digital media reflection types offered by the Responsive Mirror (previous fitting reflection and similar/dissimilar shirt reflection) higher than a plain mirror. On the other hand, neither type of digital reflection changed the appeal of the shirts nor ultimately their decision to buy a shirt.…”
Section: Summary Of User Studiesmentioning
confidence: 98%
“…In [4], we report a user study of 12 male participants using the Responsive Mirror to better understand user behaviors and their privacy sensitivities about this class of technologies. More specifically, we studied the privacy issues on sharing the images framing the questions to identify where are the typical boundary points in Irwin Altman's dimensions of privacy [1]: disclosure (what types of information would you disclose to what types of relations), projection of group and individual identity (how deep is your concern about the impression of your personal values these images of you give to others), and the temporal dimension (implications of the duration that the images will exist).…”
Section: Privacy Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous system used two cameras, a front camera to capture images and recognize classes of clothing, and an overhead camera to detect orientation toward the mirror, whereas the system we describe in this paper requires only a single camera embedded behind a halfsilvered mirror that captures frontal images of shoppers and uses a different vision algorithm to match images with similar head and body pose. Although formative trials of the system indicated some promise, the introduction of cameras into the semi-private space of evaluating clothing (though not the actual changing of clothing) is a significant hurdle for adoption of the technology [2]. The system described here is focused on a more public shopping experience which mitigates the privacy implications.…”
Section: Interactive Mirrorsmentioning
confidence: 99%